Comparison between GPS radio occultation electron densities and in situ satellite observations. Issue 6 (23rd June 2015) - Pedatella, N. M.; Yue, X.; Schreiner, W. S.
Abstract Constellation Observing System for Meteorology, Ionosphere, and Climate (COSMIC) Global Positioning System (GPS) radio occultation (RO) electron densities are compared with collocated in situ observations from the CHAllenging Minisatellite Payload (CHAMP) and Communications/Navigation Outage Forecasting System (C/NOFS) satellites. The comparison is restricted to observations occurring within 2∘ latitude and longitude and 15 min local time. The in situ observations occur at altitudes of ∼300–800 km, and the results of the present study represent the first global comparison of COSMIC electron densities at altitudes ranging from near the F region peak to the topside ionosphere. The correlation coefficient between the COSMIC and in situ observations is greater than 0.90, indicating an overall good agreement between GPS RO electron densities and CHAMP and C/NOFS satellite observations. Furthermore, when averaged over all latitudes and local times, we find a near‐zero mean bias and root‐mean‐square difference of typically less than ±30% between the COSMIC electron densities and collocated in situ observations. The overall good agreement demonstrates that the COSMIC GPS RO observations provide an accurate measure of electron density in the topside ionosphere. The results also reveal a systematic structure to the error in the equatorial and low‐latitude daytime ionosphere. This structure is related to the equatorial ionization anomaly and is consistent with the error introduced by the Abel inversion spherical symmetry assumption used to retrieve the COSMIC electron density profiles. The present study thus provides direct observational evidence of the Abel inversion error on GPS RO electron densities.